Self-assembled autonomous runners and tumblers. - Ebbens, S; Jones, R; Ryan, A; Golestanian, R; Howse, JR (2010)
A class of artificial microswimmers with combined translational and rotational self-propulsion is studied experimentally. The chemically fueled microswimmers are made of doublets of Janus colloidal beads with catalytic patches that are positioned at a fixed angle relative to one another. The mean-square displacement and the mean-square angular displacement of the active doublets are analyzed in the context of a simple Langevin description, using which the physical characteristics of the microswimmers such as the spontaneous translational and rotational velocities are extracted. Our work suggests strategies for designing microswimmers that could follow prescribed cycloidal trajectories.